(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Electric vehicle (EV) technology has gained significant attention in recent years due to its potential to mitigate environmental concerns and reduce dependency on fossil fuels. The electric motor, a crucial component of EVs, plays a pivotal role in determining the vehicle’s performance and efficiency. This paper presents a comprehensive review and comparative analysis of electric vehicle motors, focusing on their performance and efficiency characteristics. The objective is to provide a clear understanding of the different types of motors used in EVs and their corresponding advantages and limitations.